Testosterone use has been shown to affect certain physiological indicators of the liver in women after bodybuilding. - Al-Yassiri, Amir Mohsen Hussein; Al-Khafaji, Asst.L. Israa Ali Mohsen Aziz (Sulaimani Journal for Humanities, 2026)
The research problem lies in the fact that many athletes use testosterone unscientifically and without proper guidance. This is evident in their outward appearance, such as acne on the face and body, fever, hysteria, nervous disorders, heart problems, and kidney and liver issues. Therefore, the researcher decided to study this phenomenon among bodybuilders by conducting scientific laboratory analyses to document the most significant hormonal problems affecting them. The aim is to guide them toward the correct training path, free from health problems. The research aims to identify the effect of training with testosterone on certain physiological measurements of the liver in bodybuilders. The researcher used an experimental method with two groups. The research population and sample consisted of 14 bodybuilders who frequented gyms. The sample was divided into two experimental groups: the first (7) athletes used testosterone, and the second (7) athletes did not. Secrecy was maintained to identify the group using testosterone through continuous monitoring at the gym, and the second group did not use testosterone. After employing research procedures, including pre-tests and measurements, training, and post-tests and measurements, and after statistical analysis, several important conclusions emerged that benefit the training and health of bodybuilders. These conclusions included the superiority of the group using testosterone. Furthermore, the group using testosterone experienced liver damage, manifested as enlargement and an increased number of impurities, as revealed in the analyses performed on them. Therefore, the researcher recommends that athletes and coaches refrain from using testosterone due to its negative and potentially fatal consequences for physical and mental health.